2014
DOI: 10.3892/br.2014.293
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity-associated gene rs11642015 polymorphism is significantly associated with prediabetes and type 2 diabetes subsequent to adjustment for body mass index

Abstract: The association of the fat mass and obesity-associated gene () rs11642015 polymorphism with prediabetes, type 2 diabetes and obesity in certain populations has not been previously reported. A population-based study was conducted that included 490 type 2 diabetic, 471 prediabetic and 575 normal subjects. The main outcomes of the study were prediabetes, type 2 diabetes and obesity. Binary logistic regression was performed to estimate the association of rs11642015 with the risk of prediabetes, type 2 diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A few reports have shown a sex-specific effect of FTO variants on conferring susceptibility to obesity/adiposity [43,44,4649], and some reports suggest that differences in the fat distribution and/or physical activity between men and women might affect the effects of FTO variants on obesity/adiposity [4446,49]. In addition to the possible sex-specific effects, the larger sample size of men compared with women and the difference in the case/control ratio between men and women (Table 1) might lead to gender differences in the association between rs1558902 and T2D or BMI max .…”
Section: Discussionmentioning
confidence: 99%
“…A few reports have shown a sex-specific effect of FTO variants on conferring susceptibility to obesity/adiposity [43,44,4649], and some reports suggest that differences in the fat distribution and/or physical activity between men and women might affect the effects of FTO variants on obesity/adiposity [4446,49]. In addition to the possible sex-specific effects, the larger sample size of men compared with women and the difference in the case/control ratio between men and women (Table 1) might lead to gender differences in the association between rs1558902 and T2D or BMI max .…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological data has indicated that the total number of patients with diabetes may surpass 400 million by 2030 ( 1 ). Diabetes, which has become the fifth major cause of worldwide mortality after infectious disease, cardiovascular disease, cancer and trauma, is a progressive disease that is characterized by hyperglycemia ( 2 ), and may be classified into types 1 and 2 ( 2 ). The development of type 2 diabetes is associated with a high fat diet, sedentary lifestyle and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the SNP on chromosome 12 (rs1169288) that overlaps HNF1A had previously been reported as a pleiotropic variant affecting cardiometabolic traits and CRP levels [ 72 ]. The FTO variant on chromosome 16 (rs11642015) is reported as pleiotropic SNP for inflammation and lipid traits [ 73 ], and associated with BMI adjusted diabetes [ 74 ].…”
Section: Discussionmentioning
confidence: 99%